2019
DOI: 10.5863/1551-6776-24.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Health Economics and Outcomes of Surfactant Treatments for Respiratory Distress Syndrome Among Preterm Infants in US Level III/IV Neonatal Intensive Care Units

Abstract: OBJECTIVE To compare length of stay (LOS), costs, mechanical ventilation (MV), and mortality in preterm infants treated in the Neonatal Intensive Care Unit (NICU) with beractant (BE), calfactant (CA), and poractant alfa (PA) for Respiratory Distress Syndrome (RDS). METHODS This study evaluated preterm infants born between 2010 and 2013 with RDS diagnosis, gestational age of 25 to 36 weeks, birthweight of ≥500 g, and age of ≤2 days on first surfactant administration. Multivariable regression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…In RRR, the choice of surfactant is often based on pharmaceutical and financial accessibility. The type of surfactant used in RDS may be immaterial, with similar clinical outcomes and financial implications [26]. A comparison of beractant with poractant alfa, combined with nCPAP, in an RRR showed no differences in a combined outcome of death/bronchopulmonary dysplasia or other short-term outcomes [27] (Table 2).…”
Section: Rds Management In Rrr Of Ssamentioning
confidence: 99%
“…In RRR, the choice of surfactant is often based on pharmaceutical and financial accessibility. The type of surfactant used in RDS may be immaterial, with similar clinical outcomes and financial implications [26]. A comparison of beractant with poractant alfa, combined with nCPAP, in an RRR showed no differences in a combined outcome of death/bronchopulmonary dysplasia or other short-term outcomes [27] (Table 2).…”
Section: Rds Management In Rrr Of Ssamentioning
confidence: 99%
“…Surfactant treatments on patients are evaluated by cost per patient, factors that affect costs, and benchmark results. Marsh et al [ 1 ]; Brown et al [ 12 ], Zayek et al [ 13 ]; and Sekar et al [ 14 ] obtained different results in their assessments for the effective cost. Some studies focused on beractant and poractant.…”
Section: Introductionmentioning
confidence: 99%
“…When Zayek et al [ 13 ] evaluated calfactant and poractant in their study, they concluded that calfactant is cost-efficient. Sekar et al [ 14 ] concluded that the cost-effectiveness analysis of calfactant, poractant, and beractant is close, but beractant has a lower cost.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations